2019
DOI: 10.3389/fonc.2019.00853
|View full text |Cite
|
Sign up to set email alerts
|

Cinobufagin Induces Cell Cycle Arrest at the G2/M Phase and Promotes Apoptosis in Malignant Melanoma Cells

Abstract: Emerging evidence has shown that cinobufagin, as an active ingredient of Venenum Bufonis, inhibits tumor development. The aim of this study was to investigate the inhibitory effects of cinobufagin on A375 human malignant melanoma cells. MTT and colony formation assays showed that cinobufagin significantly inhibited A375 cell proliferation and cell colony formation. Additional studies demonstrated that cinobufagin markedly increased the levels of ATM serine/threonine kinase (ATM) and checkpoint kinase 2 (Chk2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 51 publications
3
52
0
Order By: Relevance
“…7B and C ). Previous studies have demonstrated that CDC25C is a cell cycle regulatory protein and serves an important role in the cell cycle ( 56 , 57 ). Thus, the effects of NCAPG-knockdown on cell cycle progression in MCF-7 cells were determined.…”
Section: Resultsmentioning
confidence: 99%
“…7B and C ). Previous studies have demonstrated that CDC25C is a cell cycle regulatory protein and serves an important role in the cell cycle ( 56 , 57 ). Thus, the effects of NCAPG-knockdown on cell cycle progression in MCF-7 cells were determined.…”
Section: Resultsmentioning
confidence: 99%
“…Cinobufagin, which was approved by the Chinese State Food and Drug Administration as a chemotherapeutic drug for liver and prostate cancer treatment in China, is a major active ingredient isolated from the Traditional Chinese Medicine Venenum Bufonis [36]. Although cytotoxic side effects in cardiac myocytes by the administration of a high dose of cinobufagin contained in Chinese Medicine has been reported [37], emerging evidence has shown that cinobufagin effectively suppresses cancer growth and progression by inducing cell cycle arrest and apoptosis and inhibiting angiogenesis [38].…”
Section: Discussionmentioning
confidence: 99%
“…This result was agreement with a previous study ( 21 ), reporting that sophoridine arrested the S phase of pancreatic cancer cell cycle. The damage and error induced by the cell cycle arrest, which occurs in the course of cell division, are difficult to repair ( 36 ). Herein, sophoridine-stimulated macrophages induced the DNA damage and cell cycle arrest, leading to the suppression of lung cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%